Prevalence of falls and its characteristics among Malaysian older adults: a review - Muhammad Iqbal Shaharudin; Bahman J; Aslinda CM (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Falls are major public health issues which highly associated with older adults worldwide. Falls can cause a negative debilitating effect on the individual and may lead to fatal injury in certain cases. Current studies on falls characteristics are limited in Malaysia. The aim of this study was to pool the current studies conducted in Malaysia regarding the fall and its characteristics. Articles were identified by using the following electronic databases; EBSCOhost, ClinicalKey, ScienceDirect, Wiley Online Library, SpringerLink and Google Scholar. Article identification was limited to English language which were published between 2013 to 2019. This study looked into older adults aged 60 years old and above; conducted either in a residential, community-dwelling or medical institute. A total of nine articles was identified and investigated. Studies indicate a huge variation in the prevalence falls among older adults in Malaysia ranging between 4-74%. A study that was conducted in the community indicated lower prevalence of falls. Majority of the falls occurred in the morning as reported by three studies which covered and ranged between 49-64.7%. Indoor accounted as the highest number of falls in term of location and ranged between 50-87% while outdoor falls were between 13-49.3%. Location in bathroom and toilet had the highest percentage of indoor falls. Fallers that sustained injury ranged between 47-82%. A variation on the fall prevalence among older adults was determined by factors such as location and existing medical conditions. Pooled information in our study indicates that there is lack of standardised measuring tools for falls characteristics in Malaysia. There is a need for large scale longitudinal prospective study to establish the prevalence and the causal-effect relationship of falls in Malaysia.